ANALISIS PENDAPATAN USAHATANI BAWANG MERAH DI DESA TONSEWER SELATAN KECAMATAN TOMPASO BARAT KABUPATEN MINAHASA - Katika Enda Ia; Caronline B. D. Pakasi; Lorraine W. Th. Sondak (Sam Ratulangi University, 2018)
This study aims to analyze the income of red onion farming in Tonsewer Village, West Tompaso Sub-district, Minahasa Regency. The data used are primary and secondary data. Primary data was obtained through prepared statement list while secondary data was obtained from BP3K West Tompaso Sub-district (Central Bureau of Statistics), internet and previous research. This research was conducted in South Tonsewer Village, West Tompaso Sub-district,which is a production center of red onion. Sample research method is done by purposive sampling (purposely), where the sample is obtained based on information from the respondents who have been interviewed. Data is presented in numerical and quantitative form. Variable measurement concept used is selling price and production costs. The results of this study indicate that the people of South Tonsewer Village rely on the field of agriculture especially the red onion, because it has a bright prospect in the sense worth to be cultivated (profitable). This can be indicated from the R / C ratio. Revenue Cost Ratio (R / C) is 1.77 of the calculation of revenue divided by total cost. This means that every Rp.1.00 cost incurred will get revenue amounting to Rp.1.77 Criteria R / C> 1 = the farmers of farmers on the farmers of red onion on the South Tonsewer beneficial.*lwths*.